Effects of Communication and Characteristics in Pekka Groups on the Economic Empowerment of Members - Kuswanti, Ana; Saleh, Amiruddin; Hubeis, Aida Vitayala S.; Puspitawati, Herien (Universitas Semarang, 2020)
The study was conducted in Batang Regency, Central Java. Still high levels of family poverty in this area, especially the condition of the family head women and tend to have non-permanent work, make the authors interested in doing this in-property research. Research methods using quantitative mixed methods are strengthened by qualitative analysis. The sampling technique uses stratified random sampling, using the Slovin formula to determine the magnitude of the number of respondents. The study population numbered 535, with a total sample of research were 229 female heads of households. The results showed that indicators of group roles and companion roles had a very large contribution in encouraging the characteristics of women's household heads to be more empowered. Through a companion role, making a family of female heads more actively communicating. Through the development of public speaking, establishing a critical culture in the group, thus growing self-confidence, forming a empowered, independent, and potential self. Important research is conducted to see the extent to which the women's head program has walked the trunk, creating many tough women. Research novelty was obtained based on a combination of group communication attributed to economic empowerment.